Analisis Kesulitan dalam Pelaksanaan Praktikum IPA SD dan IPA Terpadu SMP - Prayunisa, Fena; Marzuki, Ahmad Dedi (LPPM Institut Pendidikan Nusantara Global, 2024)
Objective Study This is Analysis Difficulty In Implementation Primary School Science and Middle School Integrated Science Practicum , Laboratory is A means supporter implementation activity incident natural in a way systematic , so IPA is not only control knowledge about incident . Type research used​ is study qualitative with method descriptive . Sample on study This is Fourth grade elementary school students and Class VII middle school students at Satap 2 Aikmel Elementary School . Research data This in the form of obstacle data implementation Practicum in elementary school and Integrated science practicum in junior high school obtained from questionnaire closed And analyzed semi - open questionnaire with descriptive qualitative as well as information obtained​ from interview . Results on indicator means infrastructure shows an average of 2 which means Still classified low . Results on indicator Knowledge shows an average ≤ 2 which means Already classified Low in matter knowledge . Results on indicator evaluation shows an average of 2.5 which means Still classified low . Results on indicator Constraint shows an average of 4-4.5 which means classified tall . Results findings on study This is quite an obstacle tall on moment implementation science practicum both in elementary and middle school, here caused Because means infrastructure For practice Still very minimal, because fund For maintenance And purchase material laboratory No sufficient. Need exists activity deepening laboratory Also to teachers for knowledge about laboratory the more Lots.